Multiple functions of α-catenin beyond cell adhesion regulation. (October 2018) - Takeichi, Masatoshi
Abstract : α-Catenin is known to play a pivotal role in cell–cell adhesion as a cytoplasmic partner for the cadherin adhesion receptors that are essential for tissue organization. The action of cadherins to firmly connect cells together depends on α-catenin; without α-catenin, cells tend to disperse. Despite this established role of α-catenin in cell junction formation, evidence has accumulated that it also plays extra-junctional roles, regulating various cell behaviors such as cell motility and polarity. Moreover, α-catenin has also been detected in non-metazoan organisms that lack cadherins, suggesting that its ancient role may not be related to cell adhesion. This article provides an overview of recent findings of such cadherin-independent functions of α-catenin, and discusses how these functions can be performed.